Valorization of Bambara groundnut shell via intermediate pyrolysis: Products distribution and characterization - Mohammed, I.Y. (Elsevier Ltd, 2016)
This study provides first report on thermochemical conversion of residue from one of the underutilized crops, Bambara groundnut. Shells from two Bambara groundnut landraces KARO and EX-SOKOTO were used. Pyrolysis was conducted in a vertical fixed bed reactor at 500, 550, 600 and 650 °C; 50 °C/min heating rate and 5 L/min nitrogen flow rate. The report gives experimental results on characteristic of the feedstock, impact of temperature on the pyrolysis product distribution (bio-oil, bio-char and non-condensable gas). It evaluates the chemical and physicochemical properties of bio-oil, characteristics of bio-char and composition of the non-condensable gas using standard analytical techniques. KARO shell produced more bio-oil and was maximum at 600 °C (37.21 wt) compared to EX-SOKOTO with the highest bio-oil yield of 32.79 wt under the same condition. Two-phase bio-oil (organic and aqueous) was collected and analyzed. The organic phase from both feedstocks was made up of benzene derivatives which can be used as a precursor for quality biofuel production while the aqueous from KARO consisted sugars and other valuable chemicals compared to the aqueous phase from EX-SOKOTO which comprised of acids, ketones, aldehydes and phenols. Characteristics of bio-char and composition of the non-condensable were also determined. The results show that bio-char is rich in carbon and some minerals which can be utilized either as a solid fuel or source of bio-fertilizer. The non-condensable gas was made up of methane, hydrogen, carbon monoxide and carbon dioxide, which can be recycled to the reactor as a carrier gas. This study demonstrated recovery of high quality fuel precursor and other valuable materials from Bambara groundnut shell. © 2016 Elsevier Ltd